2023
DOI: 10.3389/fsurg.2023.1282937
|View full text |Cite
|
Sign up to set email alerts
|

Chronic postoperative pain after non-intubated uniportal VATS lobectomy

Attila Farkas,
Tímea Csókási,
Csongor Fabó
et al.

Abstract: IntroductionPatients undergoing thoracic surgery are at increased risk of developing, long-lasting pain. Beyond the non-surgical factors, the type of operation, including the number of incisions, and the anesthetic assessment seemed to be important factors, although some studies are controversial. The aim of our study was to examine the presence of chronic postoperative pain after non-intubated uniportal VATS lobectomy. We examined the difference between the intubated, relaxed and non-intubated spontaneous ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…Our results showed the presence of mus-culoskeletal disorders in the upper limbs and limited functional capacity one year after undergoing pulmonary resection. These results were in line with previous studies that reported post-thoracotomy painful syndrome even one year after VATs lobectomy [33].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed the presence of mus-culoskeletal disorders in the upper limbs and limited functional capacity one year after undergoing pulmonary resection. These results were in line with previous studies that reported post-thoracotomy painful syndrome even one year after VATs lobectomy [33].…”
Section: Discussionsupporting
confidence: 93%